The Rhetorical Structure of Short Lecture by Famous Applied Linguists Jack C. Richards Posted on YouTube - Idham Widodo; Irma Diani; Safnil Safnil (Yayasan Karinosseff Muda Indonesia, 2020)
This study aims to investigate the rhetorical structure of move and step of short lecture by famous applied linguist Jack C. Richards posted on YouTube. The data of this study were 22 video-transcripts of a short lecture of Jack C Richards. The results: (1) three moves of rhetorical structure such as M1 – Introduction, M2 – Content of Short Lecture, and M3 – Conclusion. They are 100% occurred in all of the data analyzed as obligatory category. (2) the most often found steps in the short lectures that occurred 100% and classified as obligatory category, such as M2SB – Argumentation of the short lecture and M3SA – Summarizing the points and the steps with 60-99% percentage of occurrences as classified as conventional category, namely are M1SE – Announcing topic of oral presentation, M1SA – Greeting the Audience, M2SC – Illustration of short lecture, and M2SA – Description of short lecture. The new proposed model of spoken genre analysis adapted from Ali and Singh (2019), the Sermon model by Cheong cited in Safnil (2010) and Seliman (1996) for identifying the rhetorical structure of short lecture is effective enough to capture the possible rhetorical moves and steps in a whole text of short lecture by famous applied linguist posted in YouTube.